COMMUNITY PHARMACY PROFILE IN TEMANGGUNG REGENCY BASED ON NUMBER OF VISITORS, NUMBER OF PRESCRIPTIONS, SELF-MEDICATION SERVICES AND INCOME - LUTFIYATI, HENI; PRIBADI, PRASOJO; LATIFAH, ELMIAWATI; BUNGA, CUT DEWI (International Journal of Applied Pharmaceutics, 2025)
Objective: Pharmacy is a location for carrying out pharmaceutical tasks for pharmacists. Pharmacy also acts as a business entity that requires the application of appropriate management techniques to operate profitably and still comply with the principles of pharmaceutical service standards. The purpose of this study was to determine the profile of community pharmacies based on the number of visitors, the number of prescriptions, self-medication services and income. Methods: This study uses a quantitative approach with descriptive and correlational research designs. Descriptive aims to describe the profile of the pharmacy, the number of visitors to the pharmacy, the number of prescriptions, the number of self-medication services and the trend of pharmacy income over time. Correlational: aims to identify the relationship between the length of establishment and the ratio of pharmacies to the number of visitors and income; the relationship between the number of pharmacies and the ratio of pharmacies to the number of prescriptions. Results: Results of 57 pharmacies spread across 20 sub-districts. The largest number of pharmacies is in Temanggung District, namely 13 pharmacies with a percentage of 22.81%. However, there are still 3 sub-districts that do not have a pharmacy. Most pharmacies have an average of 30-50 patients per day and 72.73% provide self-medication services for 10-50 patients. Most pharmacies serve prescriptions<1 sheet per day. As many as 40% of pharmacies have a low income (more than Rp. 464,260 and less than Rp. 1,617,088). The results of the bivariate analysis showed that the length of establishment was related to the average income and the number of pharmacies was related to the number of prescriptions served. Conclusion: Factors related to the amount of income and the number of prescriptions are the length of establishment of the pharmacy and the number of pharmaceutical service facilities in the form of pharmacies.